Encyclopedia of knowledge management - Schwartz, David G., 1963-; Te'eni, Dov (Information Science Reference, 2011)
"This two-volume collection covers all aspects of knowledge management, which range from knowledge identification and representation, to the impact of knowledge management systems on organizational culture, to the significant integration and cost issues being faced by human resources, MIS/IT, and production departments"--Vydavatelská anotace
Keywords: znalostní management; informační management; informační sítě; učící se organizace; knowledge management; information management; information networks; organizational learning; encyklopedie; encyclopedias